Anaplasma phagocytophilum Ats-1 Is Imported into Host Cell Mitochondria and Interferes with Apoptosis Induction - Niu, Hua (Public Library of Science, 2010)
Anaplasma phagocytophilum, the causative agent of human granulocytic anaplasmosis, infects human neutrophils and inhibits mitochondria-mediated apoptosis. Bacterial factors involved in this process are unknown. In the present study, we screened a genomic DNA library of A. phagocytophilum for effectors of the type IV secretion system by a bacterial two-hybrid system, using A. phagocytophilum VirD4 as bait. A hypothetical protein was identified as a putative effector, hereby named Anaplasma translocated substrate 1 (Ats-1). Using triple immunofluorescence labeling and Western blot analysis of infected cells, including human neutrophils, we determined that Ats-1 is abundantly expressed by A. phagocytophilum, translocated across the inclusion membrane, localized in the host cell mitochondria, and cleaved. Ectopically expressed Ats-1 targeted mitochondria in an N-terminal 17 residue-dependent manner, localized in matrix or at the inner membrane, and was cleaved as native protein, which required residues 55–57. In vitro-translated Ats-1 was imported in a receptor-dependent manner into isolated mitochondria. Ats-1 inhibited etoposide-induced cytochrome c release from mitochondria, PARP cleavage, and apoptosis in mammalian cells, as well as Bax-induced yeast apoptosis. Ats-1(55–57) had significantly reduced anti-apoptotic activity. Bax redistribution was inhibited in both etoposide-induced and Bax-induced apoptosis by Ats-1. Taken together, Ats-1 is the first example of a bacterial protein that traverses five membranes and prevents apoptosis at the mitochondria.